Antecedents and outcomes of flight attendants' job satisfaction - Ng, Siew Imm; Sambasivan, Murali; Siti Zubaidah, (Elsevier, 2011)
This paper develops and tests a comprehensive model for job satisfaction amongst flight attendants with antecedents and outcomes that are germane in the context of airlines. The antecedents are: jetlag, role overload, emotional exhaustion, personal accomplishment, and depersonalization, and the outcomes are; job performance and service recovery performance. A framework was tested using structural equation modelling. A survey was conducted of flight attendants working in Malaysia found exhaustion and personal accomplishment have a direct effect on job satisfaction; emotional exhaustion and personal accomplishment affect the level of depersonalization; and role overload has a positive relationship.